Text analytics: versatile and growing - Lamont, Judith (KM world, 2013)
Text analytics is a versatile technology that is still being discovered by organizations that need to make sense of large volumes of unstructured text. It is being used in a wide variety of applications across numerous industries. The ability of text analytics to classify information is at the heart of its value proposition. Seth Earley, CEO of Earley Associates, says that search tools that auto-categorize information are using text analytics. Processes such as entity extraction, clustering and pattern detection reveal higher-order information that people were not using because they were not aware of it. An important determinant of success in using text analytics is having a solid team in place. Melissa Pippine, VP of marketing at Clarabridge, says that the team should have a clear vision not only in how the application is going to be implemented but also about why the company is doing it and how the plan will be communicated internally.